Bamboo-based agroforestry system (Dendrocalamus strictus + sesame–chickpea) for enhancing productivity in semi-arid tropics of central India - Dev, I.; Ram, A.; Ahlawat, Sudhir Pal; Palsaniya, D.R.; Singh, R.; Dhyani, S.K.; Kumar, N.; Tewari, R.K.; Singh, M.; Babanna, S.K.; Newaj, R.; Dwivedi, R.P.; et al. (Springer, 2020)
Bundelkhand region of central India is characterized by erratic rainfall with high frequency of drought. The region has undulating topography, poor groundwater resources and shallow soils with low soil fertility, resulting in frequent crop failures. A study was undertaken to assess the potential of bamboo-based agroforestry system to enhance productivity and economic returns at the research farm of ICAR-Central Agroforestry Research Institute, Jhansi (Uttar Pradesh), India, which lies in the Bundelkhand region of central India. The 7-year study (2007–2015) recorded 2906 number of bamboo culms ha−1 at 10 m × 10 m spacing compared to 2409 culms under 12 m × 10 m spacing. Averaged over 3 years (5th, 6th and 7th year), bamboo culm yield from agroforestry (Dendrocalamus strictus + Sesamum indicum–Cicer arietinum)/(bamboo + sesame–chickpea) was higher by 3.20 and 4.96% over sole bamboo in 12 m × 10 m and 10 m × 10 m, respectively. The intercrop productivity started declining from 3rd year onwards, and the extent of reduction in productivity was to the tune of 26.1, 23.7, 24.2, 17.4 and 17.4% during the 3rd, 4th, 5th, 6th and 7th year, respectively. From 5th year onwards, the harvested bamboo culms contributed to the improvement in the system productivity and it was 29 and 236% higher than the sole crops and sole bamboo, respectively, during the 7th year. Financial analysis showed that bamboo-based agroforestry system (bamboo + sesame–chickpea) planted at 12 m × 10m spacing was having high land equivalent ratio (1.95–2.14) and was more profitable than arable cropping and sole bamboo. Therefore, the Dendrocalamus strictus-based agroforestry system can be a potential alternative to arable cropping in semi-arid tropics of central India to enhance productivity and economic returns.